2021
DOI: 10.18632/aging.203479
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion practices affect CD4+ CD25+ FOXP3+ regulatory T cells/T helper-17 cells and the clinical outcome of geriatric patients with hip fracture

Abstract: Hip fracture (HF) is common among older individuals and associated with high mortality, poor vitality and functional impairment. HF patients suffer whole body immunological changes and that lead to severe consequences, including immobilization, physical impairment and a high risk of complications. The objective of this study was to decipher the pattern of dynamic immunological changes, especially in two major T cell subsets, CD4 + CD25 + FOXP3 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Cancer-associated fibroblast was reported to induce cancer cell proliferation, invasion, and metastasis through various pathways ( 28 , 29 ). Moreover, Tregs that expressed the transcription factor Foxp3 could possess importance in immune homeostasis ( 26 , 30 ). In this study, we found that LIAS expression was strongly correlated with the infiltration of immune cells, including B cell, cancer-associated fibroblast, T cell CD8+, DC, macrophage, and Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-associated fibroblast was reported to induce cancer cell proliferation, invasion, and metastasis through various pathways ( 28 , 29 ). Moreover, Tregs that expressed the transcription factor Foxp3 could possess importance in immune homeostasis ( 26 , 30 ). In this study, we found that LIAS expression was strongly correlated with the infiltration of immune cells, including B cell, cancer-associated fibroblast, T cell CD8+, DC, macrophage, and Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that LIPT2 plays a [41]. Regulatory T cells (Tregs) contribute to immune homeostasis through diverse pathways [42]. In our investigation, we explored the relationship between LIPT2 expression levels and immune infiltration across GBM, LIHC, and PCPG tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during allogeneic transfusion, Th2 cell is activated and the response of Th1 cell is thus decreased ( 23 ). Other mechanisms of immunomodulation might include the balance between T regulatory cell (Treg) and Th 17 cells: transfusion helped reverse the imbalance of Treg/Th17 ratios in hip fracture patients evidenced by the decrease and increased frequency of Tregs and Th17, respectively, after blood transfusion ( 24 ). In addition, in polytransfused sickle cell disease patients, high levels of CXCR5 + PD1 + CD4 + T lymphocyte (TL) may be a biomarker for the inhibited functions of T cells ( 25 ).…”
Section: Discussionmentioning
confidence: 99%